Autologous or allogeneic stem cell transplantation in patients with Waldenstrom’s macroglobulinemia - Anagnostopoulos, Athanasios; Hari, Parameswaran N.; Pérez, Waleska S.; Ballen, Karen; Bashey, Asad; Bredeson, Christopher N.; Freytes, César O.; Gale, Robert Peter; Gertz, Morie A.; Gibson, John; Goldschmidt, Hartmut; Lazarus, Hillard M.; et al. (Biology of blood and marrow transplantation, 2006)
The role of hematopoietic stem cell transplantation (SCT) in Waldenstrom’s macroglobulinemia (WM) has not been extensively studied. To determine the potential for long-term disease control using SCT in WM, we performed a retrospective review of 36 patients with WM who received autologous (n = 10) or allogeneic (n = 26) SCT and were reported to the Center for International Blood and Marrow Transplant Research between 1986 and 2002. The following outcomes were described: nonrelapse mortality (NRM), relapse, progression-free survival (PFS), and overall survival (OS). Median age at the time of SCT was 51 years (range, 30-76 years), and median time from initial treatment to SCT was 29 months (range, 2-198 months). A total of 78% of the patients had 2 or more previous chemotherapy regimens, and 52% had disease resistant to salvage chemotherapy. In the allogeneic SCT group, 58% of the patients received myeloablative conditioning regimens containing total body irradiation (TBI), and of the allograft recipients, 19% received nonmyeloablative/reduced-intensity conditioning. After a median follow-up of 65 months, 15 of the 36 patients (42%) are alive. Primary disease accounted for 29% of the deaths in the allogeneic SCT group and 25% of the deaths in the autologous SCT group. The relapse rate at 3 years was 29% (95% confidence interval [CI], 14%-48%) in the allogeneic group and 24% (95% CI, 4%-54%) in the autologous group. PFS at 3 years was 31% (95% CI, 14%-50%) in the allogeneic group and 65% (95% CI, 32%-91%) in the autologous group; OS was 46% (95% CI, 27%-65%) in the allogeneic group and 70% (95% CI, 40%-93%) in the autologous group. NRM at 3 years was 40% (95% CI, 23%-59%) in the allogeneic group and 11% (95% CI, 0-36%) in the autologous group. Autologous SCT is a safe and feasible treatment option for patients with WM, especially for those who present with adverse prognostic factors. Allogeneic SCT carries a much higher (40%) risk of NRM and should not be considered outside the context of a clinical trial.